Insertion Loss Reduction in SAW Device through ZnO Nanoparticle Coating toward Cell Migration Applications - Mazlee Mazalan; Mohd Hafizuddin Junaidi; A. A. M. Ezanuddin; Liew Hui Fang; Muhammad Salman Al Farisi; Do Tien Dung; Mohd Fairus Ahmad; Anas Mohd Noor; Wan Safwani Wan Kamarulzaman; Yufridin Wahab, (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
Surface acoustic waves (SAW) have been widely utilized for particle manipulation and cell migration due to their high efficiency and noninvasive nature. However, the presence of cell media and PDMS-based confined area can lead to significant insertion loss, which limits their effectiveness in biological applications. In this study, we explored the use of a ZnO nanoparticles to enhance the performance of SAW devices by reducing insertion loss for cell migration applications. Prior to fabrication, simulations were conducted to analyze the effect of the ZnO nanoparticles on the interdigital transducer (IDT). Prior to fabrication, COMSOL Multiphysics simulations showed that incorporating a ZnO layer improved in signal reflection by a 42% reduction, yielded an 18.3-fold increase in maximum surface displacement, and reduced localized mechanical stress by ~26.7%. The SAW devices were fabricated using standard microfabrication techniques, with ZnO nanoparticles deposited via sol-gel spin coating. Before depositing ZnO on IDT, the ZnO nanoparticle characteristics were confirmed by UV-Vis spectroscopy. After ZnO coating, the surface morphology was revealed by surface profiler and scanning electron microscopy (SEM). The measurement of transmission coefficient using a vector network analyzer (VNA) demonstrated approximately 80% reduction (10.06 dB) in magnitude as compared to the uncoated device. These results confirmed that the ZnO coating improves acoustic wave generation significantly and its potential for cell migration stimulation.